Fixed Points, Symmetries, and Bounds for Basins of Attraction of Complex Trigonometric Functions - Kasey Bray; Jerry Dwyer; Roger W. Barnard; G. Brock Williams (International Journal of Mathematics and Mathematical Sciences)
The dynamical systems of trigonometric functions are explored, with a focus on tz=tanz and the fractal image created by iterating the Newton map, Ftz, of  tz. The basins of attraction created from iterating  Ftz are analyzed, and some bounds are determined for the primary basins of attraction. We further prove x- and y-axis symmetry of the Newton map and explore the nature of the fractal images.